Buffering effects of social support for Indigenous males and females living with historical trauma and loss in 2 First Nation communities. Issue 2 (28th January 2019) - Bernards, Sharon; Wells, Samantha; Morton-Ninomiya, Melody; Plain, Sara; George, Tracey; Linklater, Renee; Mushquash, Christopher; George, Julie
ABSTRACT: Globally, Indigenous mental health research has increasingly focused on strengths-based theory to understand how positive factors influence wellness. However, few studies have examined how social support buffers the effects of trauma and stress on the mental health of Indigenous people. Using survey data from 207 males and 279 females in 2 Ontario First Nations we examined whether social support diminished the negative effects of perceived racism, historical trauma and loss on depression and/or anxiety. Among females, having more social supports was significantly related to a lower likelihood of depression/anxiety, whereas greater perceived racism and historical losses were associated with a greater likelihood of depression/anxiety. For both males and females, childhood adversity was significantly related to a greater likelihood of depression/anxiety. Among females, a significant interaction was found between social support and childhood adversities. For females with low social support, depression/anxiety was significantly higher among those who had experienced childhood adversities versus those with none; however, for those with high level of social support, the association was not significant. The same relationships were not found for males. Possible reasons are that males and females might experience depression/anxiety differently, or the social support measure might not adequately capture social support for First Nations males.